Avaliação da evolução clínica e dos fatores prognósticos em pacientes com epilepsia mioclônica juvenil - Guaranha, Mirian Salvadori Bittar [UNIFESP] (2010)
Purpose: To investigate if phenotypic variations including reflex traits expression have prognostic implications in Juvenile Myoclonic Epilepsy (JME). Methods: Seventy-six patients with JME underwent a video-EEG neuropsychological protocol (VNPP) and habitual methods of activation. Sixty-five of them were followed for at least three years. Reflex traits were defined as seizures and/or EEG discharges induction by eye-closure, photic stimulation, language, praxis or calculation. Patients had psychiatric evaluation and answered to STAI (State-Trait Anxiety Inventory). Seizure control was classified according to Prasad et al. (2003). Patients were divided into Group 1: good seizure control and Group 2: moderate or poor seizure control. Video-EEG/EEG evaluation was repeated after a mean of 4.4 yrs. in 21 patients. Results:. Twenty-nine out of the 76 (38.2%) presented provocative effect and inhibition was seen in 28/31 (90.3 %). Habitual methods of activation were more effective in provoking discharges than VNPP. Action-programming tasks, especially those involving manual praxis, were more effective as activation method than thinking. Inhibitory effect was higher in mental calculation. Patients with anxiety disorders had greater discharge indexes and no significant inhibitory effect on VNPP. Forty of 65 (61.5%) patients followed reached good seizure control, 25 (38.5%) of whom became seizure free. Group 2 patients had longer epilepsy duration; higher prevalence of the combination of all three seizure types; discharges in baseline EEG; seizure recording and sensitivity to praxis. Compared to seizure-free patients, those with persistent seizures presented younger age at epilepsy onset; higher prevalence of personality disorders; higher scores in STAI-Trait and higher incidence of sensitivity to praxis and to language tasks. Repetition of EEG/video-EEG suggested a parallel evolution of reflex traits disappearance and seizure control. Conclusions: Praxis exerted the most remarkable provocative effect, in accordance with the hypothesis of a motor circuitry hyperexcitability in JME. This study suggests that reflex traits expression and some other phenotypic features in JME patients have negative implications in prognosis.